Computational identification of cross-reactive TCR epitopes with ARDitox - Murcia Pienkowski, Victor; Boschert, Tamara; Skoczylas, Piotr; Sanecka-Duin, Anna; Jasiński, Maciej; Król-Józaga, Bartłomiej; Mazzocco, Giovanni; Stachura, Sławomir; Bunse, Lukas; Kaczmarczyk, Jan; Green, Edward W.; Blum, Agnieszka (Journal of cancer research and clinical oncology, 2025)
Cellular immunotherapies, such as those utilizing T lymphocytes expressing native or engineered T cell receptors (TCRs), have demonstrated therapeutic efficacy. However, some engineered high-affinity TCRs have caused fatal off-target immunotoxicity due to targeting epitopes later found to be expressed by both tumor cells and healthy tissues. Unfortunately, TCRs can be cross-reactive to epitopes with highly distinct sequences, making prediction difficult, and the exquisite sequence specificity of TCRs means that safety studies in mice miss human-specific epitopes.